2015
DOI: 10.3762/bjnano.6.143
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment of magnetite nanoparticles

Abstract: SummaryThis paper presents the results of a thermal treatment process for magnetite nanoparticles in the temperature range of 50–500 °C. The tested magnetite nanoparticles were synthesized using three different methods that resulted in nanoparticles with different surface characteristics and crystallinity, which in turn, was reflected in their thermal durability. The particles were obtained by coprecipitation from Fe chlorides and decomposition of an Fe(acac)3 complex with and without a core–shell structure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 49 publications
2
38
0
1
Order By: Relevance
“…Even if FESEM analysis evidenced the presence of magnetite nucleated around metallic silver particles, which can have a nucleating effect [34], it seems that silver influenced the place of nucleation and the shape of crystals but not the quantity of crystalline phase. The amount of magnetite observed in the bulk samples (both SC45 and Ag-SC45) is slightly lower respect the samples in powders form; these results can be explained considering that bulk samples were subjected to an annealing at 600°C and at this temperature the transformation magnetite-hematite can occur [41]. In any case, the magnetite amount is in accordance with the results obtained by Bruno et al [16] for the pure SC45.…”
Section: Characterizations Of Ag-sc45supporting
confidence: 90%
“…Even if FESEM analysis evidenced the presence of magnetite nucleated around metallic silver particles, which can have a nucleating effect [34], it seems that silver influenced the place of nucleation and the shape of crystals but not the quantity of crystalline phase. The amount of magnetite observed in the bulk samples (both SC45 and Ag-SC45) is slightly lower respect the samples in powders form; these results can be explained considering that bulk samples were subjected to an annealing at 600°C and at this temperature the transformation magnetite-hematite can occur [41]. In any case, the magnetite amount is in accordance with the results obtained by Bruno et al [16] for the pure SC45.…”
Section: Characterizations Of Ag-sc45supporting
confidence: 90%
“…Dehydration of coagulated complexes based on iron hydroxides or/and oxyhydroxides is followed by iron oxide formation [6,8]. High temperature dehydration and oxidation of iron oxides, hydroxides are followed by several temperature-dependent phase interchanges between phases hematite-maghemite-magnetite [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In oxygen-rich atmosphere, magnetite usually goes through several temperature-dependent stages during rapid oxidation [10][11][12] It can be concluded that increasing temperature favours the oxidative magnetite/maghemite transformation toward hematite formation.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal decomposition of all sample at this temperature are decreasing, this shows that all the decomposition stopped. In addition, at temperature 500°C, the magnetite is changed into hematite 48 .…”
Section: -Gptms-argmentioning
confidence: 99%